THE DESIGN OF TOPSIS4BIM DECISION SUPPORT FOR BUILDING INFORMATION MODELING SOFTWARE SELECTION (Jurnal Teknologi (Sciences & Engineering), 2015)
The emerging of new Information Communication Technology (ICT) technology namely Building Information Modeling been proven benefits toward construction industry. As a result, the list of BIM software available in the market is keep increasing in recent years. This has led to the selection problem among construction companies. Moreover, the selection BIM software also required high investment in term of software, hard ware and training expenses. These aforementioned issues have increased the complexities of decision process and the need of decision aid in BIM software selection. Thus, this paper has introduced a new approach in MCDMDSS web development by utilization of Web 2.0 application. The rapid development of Information technology has highly benefit to the development of web based DSS. The design and validation architecture of a web base DSS called topsis4BIM for Building Information Modeling (BIM) is presented.Â